Hadith Selection Methods in the Study of Sirah Nabawiyyah (An Analysis of Shahih Sirah Nabawiyyah by Akram Dhiya al-‘Umari) - Acep Dani (International Journal of Nusantara Islam, 2017)
The Shahih Sirah Nabawiyyah by Akram Dhiya al‘Umari is one of the contemporary books of sirah. This research aims to find out the methods of selecting hadiths in sirah nabawiyyah according to Akram Dhiya al-‘Umari. The research is based on the accepted principle of hadith studies that hadith used as hujjah is authentic (shahih) hadiths. If there is no authentic hadith, weak (dhaif) hadiths can be used as long as it is not related to the issues of beliefs (aqeedah) and law. This research concludes that the hadith selection method in sirah nabawiyyah used by Akram Dhiya al-‘Umari is the method of hadith scholars which is flexible in treating the weak hadiths. In sirah nabawiyyah, al-’Umari still prioritizes the authentic hadith as the main source. If the authentic hadith about an issue is not found, the weak hadith can be used. However, it shall be noted that the hadith should not be related to the issues of beliefs (aqeedah) and law.